IMPLEMENTASI METODE TALAQQI DALAM MENINGKATKAN KULITAS BACAAN AL-QUR’AN SANTRI DI PONDOK PESANTREN AL AQOBAH 4 DIWEK JOMBANG - Siti Aisyah; Lailatul Qomariyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the implementation of the talaqqi method in improving the quality of Qur’anic recitation among students at Pondok Pesantren Al Aqobah 4 Diwek Jombang. The background of this research stems from the importance of reading the Qur’an correctly in accordance with the rules of tajwid and makhraj, which many students still struggle with. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings reveal that the talaqqi method is implemented through a direct process between teacher and student, starting with the teacher demonstrating the recitation, followed by group repetition by students, and individual recitation in front of the teacher. The method proves effective, as students show significant improvement in the accuracy of their recitation, particularly in tajwid and makhraj. Supporting factors include teachers with authentic sanad, innovative teaching styles, and a conducive learning environment. Hindering factors include a lack of student motivation, insufficient communication between teachers and students, and varying levels of comprehension. This study implies that the talaqqi method can serve as an effective strategy in Qur’anic learning to enhance students’ reading proficiency.